Body and Machine in Classical Antiquity - Gerolemou, Maria (Cambridge University Press, 2023)
The first systematic exploration of the multifaceted relationship between human bodies and machines in classical antiquity
Description based on publisher supplied metadata and other sources
Keywords: Human body and technology; Technology-Greece-History-To 1500; Medicine, Greek and Roman; Human body and technology in literature; Künstlicher Mensch; Antike; Mechanik; Automat; Medizin; Körper; Konferenzschrift -- Universität Zypern -- 01.12.2017 -- Nikosia